Acupuncture therapy for treating postherpetic neuralgia: A protocol for an overview of systematic reviews and meta-analysis - Yu, Jie (Medicine (Baltimore), 2020)
BACKGROUND: Postherpetic neuralgia (PHN) is the most common complication and sequela of herpes zoster (HZ) that greatly affects the life and emotional experience of patients. Acupuncture therapy has been confirmed as an effective and safe treatment for PHN. Several systematic reviews (SRs) and meta-analysis (MAs) have reported the evidence of acupuncture therapy for treating PHN. However, the evidence has not been systematically synthesized. This overview aims to synthesize and assess the reliability of evidence generated from these SRs and MAs of acupuncture therapy for PHN. METHODS: We will conduct a systematic search of the China Biology Medicine (CBM), VIP database, Wangfang database, China National Knowledge Infrastructure (CNKI), Pubmed, Cochrane Library, Excerpt Medical Database (Embase), and Web of Science to identify eligible SRs and MAs, from their inception to October 31, 2020. We will use Assessment of Multiple Systematic Reviews-2 (AMSTAR2) for methodological quality assessment, Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) for report quality assessment, Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) for the quality of evidence assessment, and ROBIS for the bias assessment. Our reviewers will conduct systematic reviews, qualification evaluation, data extraction, methodological quality, and evidence quality screening in pairs. The outcomes include pain intensity, Quality of life (QoL), Hamilton Anxiety Scale (HAMA), Global impression, and adverse events. All the extracted data will be provided in tabular form to summarize characteristics of each review. The evidence will be a narrative synthesis of the type and content of the intervention and the results reported. RESULTS: The results of this study will be published in a peer-reviewed journal. CONCLUSIONS: This overview will provide comprehensive evidence of acupuncture therapy for patients with PHN. ETHICS AND DISSEMINATION: This review will not involve private information of participants, so the ethical approval will not be required. The results will be disseminated in a peer-reviewed journal or conference presentation. Important protocol modifications will be updated on PROSPERO. PROSPERO REGISTRATION NUMBER: CRD42020178738.